Spine Surgery : A Case-Based Approach / Bernhard Meyer, Michael Rauschmann editors - Meyer, Bernhard Editors
This book covers the content of European postgraduate spine surgery courses, using a case-based approach. A step-wise solution to a real clinical problem is described and compared to the best available evidence. A weighted conclusion is provided on how to bridge the gap (if there is one) between standard of care and evidence-based medicine. Spine Surgery: A Case-Based Approach is aimed at postgraduate students of spine surgery (both trainee neurosurgeons and trainee orthopedic surgeons), and may also be of interest to medical students.